1997
DOI: 10.1097/00001756-199704140-00022
|View full text |Cite
|
Sign up to set email alerts
|

Increased cerebral choline-compounds in Duchenne muscular dystrophy

Abstract: We investigated the hypothesis that cell membrane function is abnormal in brains of subjects with Duchenne muscular dystrophy (DMD) using proton-nuclear magnetic resonance (NMR) spectroscopy of human brain extracts. The total amount of choline-containing compounds was significantly higher (about three times) than in normal controls and patients with other myopathies, while N-acetyl-L-aspartic acid and creatine were within the normal range. These findings indicate that abnormal cell membrane function may be cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 7 publications
3
13
1
1
Order By: Relevance
“…Sporadic research has been conducted examining genotype-phenotype associations, histology, and biochemistry of the central nervous system (CNS), and corticoelectrophysiology in children with DMD. Anomalies found in the CNS of children with DMD have included: neuronal loss (Jagadha and Becker 1988); Purkinje cell loss (Jagadha and Becker 1988); macroglossia (Bresolin et al 1994); gliosis (Jagadha and Becker 1988); neurofibrillary tangles (Jagadha and Becker 1988); dendritic abnormalities (Jagadha and Becker 1988); heterotopias (Jagadha and Becker 1988); mild to severe cortical atrophy (Yoshioka et al 1980, Septien et al 1991; ventricular enlargement (Yoshioka et al 1980, Septien et al 1991; increased head circumference (Appleton et al 1991); elevated levels of inorganic phosphate (Tracey et al 1995); and choline-containing compounds (Kato et al 1997). Cognitive impairments have also been reported to relate to the presence of a mutation in the Dp71 (Moizard et al 1998(Moizard et al , 2000 and Dp120 dystrophin isoforms (Lidov et al 1995, Morris et al 1995, Moizard et al 1998, Felisari et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Sporadic research has been conducted examining genotype-phenotype associations, histology, and biochemistry of the central nervous system (CNS), and corticoelectrophysiology in children with DMD. Anomalies found in the CNS of children with DMD have included: neuronal loss (Jagadha and Becker 1988); Purkinje cell loss (Jagadha and Becker 1988); macroglossia (Bresolin et al 1994); gliosis (Jagadha and Becker 1988); neurofibrillary tangles (Jagadha and Becker 1988); dendritic abnormalities (Jagadha and Becker 1988); heterotopias (Jagadha and Becker 1988); mild to severe cortical atrophy (Yoshioka et al 1980, Septien et al 1991; ventricular enlargement (Yoshioka et al 1980, Septien et al 1991; increased head circumference (Appleton et al 1991); elevated levels of inorganic phosphate (Tracey et al 1995); and choline-containing compounds (Kato et al 1997). Cognitive impairments have also been reported to relate to the presence of a mutation in the Dp71 (Moizard et al 1998(Moizard et al , 2000 and Dp120 dystrophin isoforms (Lidov et al 1995, Morris et al 1995, Moizard et al 1998, Felisari et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Creatine, taurine, and choline-containing metabolites have been reported to be altered in concentration in dystrophic tissue in previous studies in muscle (9,20) and brain (10,12,13,21). However, these studies investigated only a small number of metabolites and often in only one tissue type.…”
Section: Discussionmentioning
confidence: 99%
“…Other areas of the brain did not show any significant increase at this age group. An increase in choline-containing compounds is also seen in boys older than 17 years in the prefrontal cortex (Kato et al, 1997). Rae et al (2002), in their paper on biochemical abnormalities of the mdx brain, have suggested that these alterations in the cerebellum and the hippocampus could imply a compensation mechanism.…”
Section: Alterations Due To Lack Of Dystrophinmentioning
confidence: 99%